2024
DOI: 10.3390/nu16071088
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and Recurrent Major Cardiovascular Events Following Acute Myocardial Infarction—A Follow-Up Study in a Primary Percutaneous Coronary Intervention Center

Maria Czinege,
Vasile-Bogdan Halațiu,
Victoria Nyulas
et al.

Abstract: Background: Acute myocardial infarction is often accompanied by malnutrition, which is associated with an imbalance between catabolic and anabolic processes. This ultimately leads to cardiac cachexia, which worsens the patient’s prognosis. We aimed to assess the correlation between nutritional status, assessed using the controlling nutritional status (CONUT) score, and the rate of major cardiovascular adverse events (MACE). Methods: The present investigation was a non-randomized, prospective, observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several studies have reported that CONUT is linked to the mortality of diseases like chronic heart failure and malignant tumors, as well as postoperative outcomes in cardiovascular and gastrointestinal surgery [17][18][19]. Other studies have reported an association with the incidence of major acute cardiovascular events (MACEs) in patients after acute myocardial infarction [20]. The CONUT score has been extensively studied in a variety of pathologies, including in post-surgical patients and those with malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that CONUT is linked to the mortality of diseases like chronic heart failure and malignant tumors, as well as postoperative outcomes in cardiovascular and gastrointestinal surgery [17][18][19]. Other studies have reported an association with the incidence of major acute cardiovascular events (MACEs) in patients after acute myocardial infarction [20]. The CONUT score has been extensively studied in a variety of pathologies, including in post-surgical patients and those with malignancies.…”
Section: Introductionmentioning
confidence: 99%